Red fluorescent glass material as well as method and application thereof

By adopting specific chemical composition and heat treatment steps, a red fluorescent glass material with high visible light transmittance and luminous intensity was prepared, which solved the problem of poor light transmittance in the prior art, and achieved the effect of efficiently emitting red fluorescence under blue light excitation.

CN119638195AActive Publication Date: 2025-03-18BAOTOU RESEARCH INSTITUTE OF RARE EARTHS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411892587.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

There are many components that emit red fluorescent glass materials that emit red fluorescence under blue light excitation, resulting in poor light transmittance and it is difficult to reduce components while having high luminous intensity and high light transmittance.

Method used

A red fluorescent glass material with a chemical composition aMO·bY2O3·cSiO2·dRO2·xEu2O3, wherein M is selected from Ca, Sr and Ba, and R is selected from Zr, Ti and Ge. A red fluorescent glass with high visible light transmittance and luminous intensity is prepared through a specific molar fraction range and heat treatment steps.

Benefits of technology

A red fluorescent glass material that emits red fluorescence under blue light excitation has a high visible light transmittance and luminous intensity, while reducing the use of components. The emission spectrum ranges from 570 to 630 nm and the emission peak wavelength is 613 nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638195A_ABST
    Figure CN119638195A_ABST
Patent Text Reader

Abstract

The invention discloses a red fluorescent glass material as well as a method and application thereof. The red fluorescent glass material has a chemical composition shown as a formula (1): aMO.bY2O3.cSiO2.dRO2.xEu2O3 (1), M is selected from one or more of Ca, Sr and Ba, and R is selected from one or more of Zr, Ti and Ge; a represents the molar coefficient of MO, 0 lt; a < lt >; 1; b represents the molar coefficient of Y2O3, 0 lt; blt; 1; c represents the molar coefficient of SiO2, 0 lt; clt; ct; 1; d represents the molar coefficient of RO2, 0 lt; dlt; 1; x represents the molar coefficient of Eu2O3, 0 lt; xlt; and 0.1. The red fluorescent glass material disclosed by the invention can emit red fluorescence under the excitation of blue light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a red fluorescent glass material, a method and an application thereof. Background Art

[0002] Fluorescent glass refers to a luminescent material prepared by doping phosphors into a glass matrix. It has the optical properties of phosphors and the heat resistance and transparency of glass. In LED applications, it can avoid problems such as aging and efficiency reduction caused by silicone encapsulation.

[0003] Red fluorescent glass can be used in the white light LED industry to supplement the red light part of the blue light LED + YAG:Ce packaged lamps, solve the problem of red light deficiency, and improve the color rendering index of white light LEDs. White light LED generally refers to the yellow light emitted by YAG fluorescent powder stimulated by the blue light LED chip, which is mixed with the remaining blue light to form white light. The full name of YAG fluorescent powder is yttrium aluminum garnet fluorescent powder.

[0004] CN109628092A discloses a red light phosphor doped with europium ions for white light LEDs, and its chemical composition is as follows: CaY 2-x-y Ln y Ge 4-z M z O 12 :xEu 3+ , Ln is one or more of Sc, Gd and La, and M is one of Si and Ti. Under the excitation of near-ultraviolet light, the phosphor can emit red fluorescence covering the range of 550 to 700 nm with a main luminescence peak at 612 nm.

[0005] CN107827354A discloses a red fluorescent glass, which is made of the following effective materials: a matrix glass component raw material and CaSrAlSiN with a mass fraction of 1:0.002-0.01. 3 :Eu 2+ Phosphor, wherein the matrix glass component raw material is 10-50 mol% Bi with a molar fraction of 100% 2 O 3 、30~80mol%B 2 O 3 , 5-10 mol% ZnO and 5-10 mol% Al 2 O 3 The excitation wavelength of the red fluorescent glass is 470nm, and the light transmittance is poor.

[0006] CN113387568A discloses a red fluorescent glass having the following composition: aCaO: bY 2 O 3 :cT 2 O:dSiO2 : eZO 2 : nPr 6 O 11 : xEr 2 O 3 , T is selected from one or more of Li, Na, and K; Z is selected from one or more of Zr, Ti, and Ge; a, b, c, d, e, n, and x represent the molar fractions of each component; 0 < a < 1, 0 < b < 1, 0 < c < 1, 0 < d < 1, and 2a + b + c = 4(d + e); n = (0.0001 - 0.1) / 6; x = (0.0001 - 0.1) / 2. The components in this red fluorescent glass are slightly more, and moreover, the heavy rare earth element erbium is used.

[0007] CN113387562A discloses a rare earth - doped red fluorescent glass and its preparation process. The rare earth - doped red fluorescent glass has a chemical composition represented by (MO)x(Y 2 O 3 )y(T 2 O)z(SiO 2 )a(EO 2 )b(Pr 6 O 11 )c(Eu 2 O 3 )d; wherein, M is selected from at least one of Mg or Ba; T is selected from at least one of Li, Na, and K; E is selected from at least one of Zr, Ti, and Ge; x, y, z, a, b, c, and d respectively represent the molar fractions of MO, Y 2 O 3 , T 2 O, SiO 2 , EO 2 , Pr 6 O 11 and Eu 2 O 3 ; x is 0.0001 - 0.5, y is 0.5 - 0.99, z is 0.001 - 0.3, a is 0.01 - 0.6, b is 0.0001 - 0.2, c is 0.00001 - 0.001, and d is 0.00001 - 0.001. The components of this red fluorescent glass are still relatively many. SUMMARY OF THE INVENTION

[0008] In view of this, an object of the present invention is to provide a red fluorescent glass material that can emit red fluorescence under the excitation of blue light, has a higher visible light transmittance and luminous intensity, and uses fewer components.

[0009] Another object of the present invention is to provide a method for preparing the above - mentioned red fluorescent glass material.

[0010] Another object of the present invention is to provide the use of the red fluorescent glass material as described above.

[0011] The present invention adopts the following technical solutions to achieve the above object.

[0012] On the one hand, the present invention provides a red fluorescent glass material having a chemical composition as shown in formula (1):

[0013] aMO·bY 2 O 3 ·cSiO 2 ·dRO 2 ·xEu 2 O 3 (1),

[0014] Wherein,

[0015] M is selected from one or more of Ca, Sr, and Ba, and R is selected from one or more of Zr, Ti, and Ge;

[0016] a represents the molar coefficient of MO, 0 < a < 1; b represents the molar coefficient of Y 2 O 3 ; c represents the molar coefficient of SiO 2 ; d represents the molar coefficient of RO 2 ; x represents the molar coefficient of Eu 2 O 3 , 0 < x < 0.1.

[0017] According to the red fluorescent glass material of the present invention, preferably, M is selected from one of Ca, Sr, and Ba.

[0018] According to the red fluorescent glass material of the present invention, preferably, R is selected from one of Zr, Ti, and Ge.

[0019] According to the red fluorescent glass material of the present invention, preferably, 0.1 < a < 0.9, 0.05 < b < 0.5.

[0020] According to the red fluorescent glass material of the present invention, preferably, 0.05 < c < 1, 0.01 < d < 0.9.

[0021] According to the red fluorescent glass material of the present invention, preferably, 0.005 < x < 0.1.

[0022] According to the red fluorescent glass material of the present invention, preferably, it has any one of the following chemical compositions:

[0023] 0.7CaO·0.15Y 2 O3 0.8SiO 2 0.2GeO 2 0.035Eu 2 O 3 ;

[0024] 0.7CaO·0.15Y 2 O 3 0.9SiO 2 0.1GeO 2 0.035Eu 2 O 3 ;

[0025] 0.7CaO·0.15Y 2 O 3 0.7SiO 2 0.3GeO 2 0.035Eu 2 O 3 ;

[0026] 0.7CaO·0.15Y 2 O 3 0.6SiO 2 0.4GeO 2 0.035Eu 2 O 3 ;

[0027] 0.7CaO·0.15Y 2 O 3 0.5SiO 2 0.5GeO 2 0.035Eu 2 O 3 .

[0028] On the other hand, the present invention also provides a method for preparing the red fluorescent glass material as described above, comprising the following steps:

[0029] 1) mixing the raw materials according to the chemical composition to obtain a mixture; calcining the mixture at 1200-1800° C. for 1-10 hours to obtain a calcination product;

[0030] 2) pouring the calcined product to obtain a glass product;

[0031] 3) The glass product is further heat treated at 300-800° C. to obtain a red fluorescent glass material.

[0032] According to the method of the present invention, preferably, the burning temperature is 1300-1700° C., and the burning time is 1-8 hours.

[0033] On the other hand, the present invention also provides a use of the red fluorescent glass material as described above in the packaging of light-emitting diodes.

[0034] The red fluorescent glass material of the present invention can emit red fluorescence under blue light excitation, and has fewer components on the basis of having a relatively high visible light transmittance. The emission spectrum ranges from 570 to 630 nm, and the emission peak wavelength is at 613 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a physical picture of the red fluorescent glass material obtained in Example 1.

[0036] Figure 2 It is an emission spectrum diagram of the red fluorescent glass material obtained in Example 1.

[0037] Figure 3 It is an excitation spectrum diagram of the red fluorescent glass material obtained in Example 1.

[0038] Figure 4 It is a visible light transmittance test curve of the red fluorescent glass material obtained in Example 1. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0039] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0040] The red fluorescent glass material of the present invention can emit red fluorescence under blue light excitation, and has fewer components on the basis of having a relatively high visible light transmittance and luminous intensity.

[0041] <Red fluorescent glass material>

[0042] A red fluorescent glass material provided by the present invention has a chemical composition as shown in formula (1):

[0043] aMO·bY 2 O 3 ·cSiO 2 ·dRO 2 ·xEu 2 O 3 (1),

[0044] wherein, M is selected from one or more of Ca, Sr, and Ba, and R is selected from one or more of Zr, Ti, and Ge; a represents the molar coefficient of MO, 0 < a < 1; b represents the molar coefficient of Y 2 O 3 , 0 < b < 1; c represents the molar coefficient of SiO 2 of, 0 < c < 1; d represents the molar coefficient of RO 2 of, 0 < d < 1; x represents Eu2 O 3 The molar coefficient of, 0 < x < 0.1. Such a red fluorescent glass material can emit red fluorescence under the excitation of blue light, with high visible light transmittance, luminous intensity, and high transparency.

[0045] The red fluorescent glass material of the present invention consists only of the above components and inevitable impurities, and does not contain Pr 6 O 11 , Li 2 O, Na 2 O, K 2 O. Compared with the prior art CN113387562A, the present invention omits praseodymium oxide and alkali metal oxides, emits red fluorescence under the excitation of blue light, and the visible light transmittance is also improved, which does not belong to a conventional choice.

[0046] The red fluorescent glass of the present invention can be excited by blue light of 465 nm. The range of the emission spectrum is 570 - 630 nm.

[0047] According to a specific embodiment of the present invention, under the excitation of blue light with a wavelength of 465 nm, the emission peak wavelength of the emission spectrum is at 613 nm.

[0048] In the present invention, M can be selected from one or more of Ca, Sr, and Ba, preferably selected from one of Ca, Sr, and Ba. Ca is the calcium element, Sr is the strontium element, and Ba is the barium element. a represents the molar coefficient of MO, 0 < a < 1, preferably, 0.1 < a < 0.9, more preferably, 0.3 < a < 0.9, still more preferably, 0.5 < a < 0.9. For example, a can be 0.5, 0.6, 0.7, 0.8. Such a range is more conducive to making the obtained red fluorescent glass material emit red fluorescence under the excitation of blue light and have a higher luminous intensity.

[0049] In the present invention, Y 2 O 3 is yttrium oxide. b represents the molar coefficient of Y 2 O 3 , 0 < b < 1, preferably, 0.05 < b < 0.5, more preferably, 0.08 < b < 0.4, still more preferably, 0.09 < b < 0.3. For example, b can be 0.1, 0.15, 0.2.

[0050] In the present invention, SiO 2 is silicon dioxide. c represents the molar coefficient of SiO 2 , 0 < c < 1, preferably, 0.05 < c < 1, more preferably, 0.1 < c < 1, still more preferably, 0.2 < c < 1. For example, c can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9.

[0051] In the present invention, R is selected from one or more of Zr, Ti, and Ge, preferably selected from one of Zr, Ti, and Ge, and more preferably Ge. Zr is the zirconium element. Ti is the titanium element. Ge is the germanium element.

[0052] In the present invention, d represents the molar coefficient of RO 2 , where 0 < d < 1. Preferably, 0.01 < d < 0.9. More preferably, 0.05 < d < 0.9. Still more preferably, 0.07 < d < 0.8. For example, d can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7. These elements can regulate and affect the crystal field environment around the activator ions, thereby enhancing the fluorescence emission efficiency.

[0053] In the present invention, Eu 2 O 3 is europium trioxide. x represents the molar coefficient of Eu 2 O 3 , where 0 < x < 0.1. Preferably, 0.005 < x < 0.1. More preferably, 0.008 < x < 0.09. Still more preferably, 0.01 < x < 0.08. For example, x is 0.035. This is beneficial for obtaining better fluorescence emission intensity of the resulting red fluorescent glass material under the excitation of blue light.

[0054] According to a preferred embodiment of the present invention, the red fluorescent glass material has a chemical composition as shown in formula (1):

[0055] aMO·bY 2 O 3 ·cSiO 2 ·dRO 2 ·xEu 2 O 3 (1),

[0056] wherein, M is selected from one or more of Ca, Sr, and Ba, and R is selected from one or more of Zr, Ti, and Ge; a represents the molar coefficient of MO, 0.5 < a < 1; b represents the molar coefficient of Y 2 O 3 , 0.05 < b < 0.5; c represents the molar coefficient of SiO 2 , 0.1 < c < 1; d represents the molar coefficient of RO 2 , 0.05 < d < 0.9; x represents the molar coefficient of Eu 2 O 3 , 0.005 < x < 0.1.

[0057] According to a specific embodiment of the present invention, the red fluorescent glass material has the following chemical composition: 0.7CaO·0.15Y 2 O 3 0.8SiO 2 0.2GeO 2 0.035Eu 2 O 3 .

[0058] According to another specific embodiment of the present invention, the red fluorescent glass material has the following chemical composition: 0.7CaO·0.15Y 2 O 3 0.9SiO 2 0.1GeO 2 0.035Eu 2 O 3 .

[0059] According to another specific embodiment of the present invention, the red fluorescent glass material has the following chemical composition: 0.7CaO·0.15Y 2 O 3 0.7SiO 2 0.3GeO 2 0.035Eu 2 O 3 .

[0060] According to another specific embodiment of the present invention, the red fluorescent glass material has the following chemical composition: 0.7CaO·0.15Y 2 O 3 0.6SiO 2 0.4GeO 2 0.035Eu 2 O 3 .

[0061] According to another specific embodiment of the present invention, the red fluorescent glass material has the following chemical composition: 0.7CaO·0.15Y 2 O 3 0.5SiO 2 0.5GeO 2 0.035Eu 2 O 3 .

[0062] <Preparation method>

[0063] The present invention also provides a method for preparing the red fluorescent glass material as described above, comprising the following steps: 1) mixing and burning step; 2) casting and molding step; 3) heat treatment step, which is described in detail below.

[0064] Mixing and burning steps

[0065] According to the chemical composition shown in formula (1), various raw materials are mixed to obtain a mixture; the mixture is calcined at 1200-1800° C. for 1-10 hours to obtain a calcined product.

[0066] The raw material source of MO in formula (1) can be an oxide, carbonate, sulfate, nitrate or hydroxide of M, preferably an oxide of M.

[0067] Y in formula (1) 2 O 3 The raw material source can be yttrium trioxide or yttrium carbonate.

[0068] SiO in formula (1) 2 The raw material source can be silicon dioxide or silicate.

[0069] GeO in formula (1) 2 The raw material source of can be germanium dioxide or germanium salts, and the germanium salts can be germanium carbonate, germanium sulfate, germanium nitrate, etc. 2 O 3 The source of europium can be europium trioxide or europium salts. The europium salts can be, for example, europium carbonate, europium nitrate or europium sulfate.

[0070] According to a specific embodiment of the present invention, according to the molar ratio, corresponding amounts of calcium oxide (CaO), yttrium trioxide (Y 2 O 3 ), silicon dioxide (SiO 2 ), Germanium dioxide (GeO 2 ), europium trioxide (Eu 2 O 3 )mix.

[0071] In the present invention, the calcination temperature may be 1200 to 1800° C., preferably 1300 to 1700° C., more preferably 1400 to 1600° C. The calcination time may be 1 to 10 hours, preferably 1 to 8 hours, more preferably 1 to 5 hours.

[0072] Casting steps

[0073] The calcined product is poured to obtain a glass product. According to a specific embodiment of the present invention, the calcined product is poured into a mold to form a glass product.

[0074] Heat treatment steps

[0075] The glass product is further heat treated to obtain a red fluorescent glass material, which is conducive to obtaining a red fluorescent glass material with stable performance.

[0076] In the present invention, the temperature of the further heat treatment can be 300-800° C., preferably 400-700° C., more preferably 500-600° C. The heat treatment time can be 1-20 hours, preferably 2-18 hours, more preferably 5-8 hours. This is conducive to eliminating internal stress and obtaining a red fluorescent glass material with stable performance.

[0077] <Purpose>

[0078] The present invention also provides a use of the red fluorescent glass material, specifically, a use in light emitting diode packaging. The obtained red fluorescent glass is cut and polished, and then packaged in a YAG+blue light chip lamp bead using a covering packaging method to play a role in supplementing red light.

[0079] Test method:

[0080] Relative luminous intensity: Use a fluorescence spectrometer to select 465nm blue light to excite the red fluorescent glass material. By integrating the emission spectrum or selecting the intensity value at a specific wavelength and comparing it with the standard sample, the relative luminous intensity of the fluorescent glass can be characterized.

[0081] Visible light transmittance: Use a spectrophotometer to generate visible light of continuous wavelength, measure the intensity ratio of the light passing through the fluorescent glass and the reference light, and obtain the visible light transmittance of the fluorescent glass.

[0082] Example 1

[0083] In this embodiment, the chemical composition of the red fluorescent glass material is 0.7CaO·0.15Y 2 O 3 0.8SiO 2 0.2GeO 2 0.035Eu 2 O 3 .

[0084] The preparation steps are as follows: weigh the corresponding weights of CaO (analytical grade), Y 2 O 3 (analytical pure), SiO 2 (analytical grade), GeO 2 (purity 99.99%), Eu 2 O 3 (purity 99.99%), the weighed raw materials were put into an agate mortar and mixed evenly to obtain a mixture.

[0085] The mixture was placed in a crucible, heated to 1550°C in a resistance furnace, and fired at 1550°C for 1 hour to obtain a fired product. The fired product was poured into a preheated mold to obtain a molded red fluorescent glass material.

[0086] The formed red fluorescent glass material is heat-treated at 500° C. for 5 hours to eliminate the internal stress of the red fluorescent glass material, thereby obtaining the red fluorescent glass material.

[0087] The prepared red fluorescent glass material is as follows Figure 1 As shown (physical picture). Figure 1 It can be seen that the red fluorescent glass material obtained in this embodiment has good visible light transmittance and high transparency.

[0088] Example 2

[0089] In this embodiment, the chemical composition of the red fluorescent glass material is 0.7CaO·0.15Y 2 O 3 0.9SiO 2 0.1GeO 2 0.035Eu 2 O 3 The corresponding raw materials were weighed according to the chemical composition. The remaining operation steps and process parameters were the same as those in Example 1.

[0090] Example 3

[0091] In this embodiment, the chemical composition of the red fluorescent glass material is 0.7CaO·0.15Y 2 O 3 0.7SiO 2 0.3GeO 2 0.035Eu 2 O 3 The corresponding raw materials were weighed according to the chemical composition. The remaining operation steps and process parameters were the same as those in Example 1.

[0092] Example 4

[0093] In this embodiment, the chemical composition of the red fluorescent glass material is 0.7CaO·0.15Y 2 O 3 0.6SiO 2 0.4GeO 2 0.035Eu 2 O 3 The corresponding raw materials were weighed according to the chemical composition. The remaining operation steps and process parameters were the same as those in Example 1.

[0094] Example 5

[0095] In this embodiment, the chemical composition of the red fluorescent glass material is 0.7CaO·0.15Y 2 O 3 0.5SiO 2 0.5GeO 2 0.035Eu 2 O 3 The corresponding raw materials were weighed according to the chemical composition. The remaining operation steps and process parameters were the same as those in Example 1.

[0096] Comparative Example 1

[0097] In this embodiment, the chemical composition of the fluorescent glass material is 0.7CaO·0.15Y 2 O 3 ·SiO 2 0.035Eu 2 O 3 The corresponding raw materials were weighed according to the chemical composition. The remaining operation steps and process parameters were the same as those in Example 1.

[0098] Performance Testing

[0099] The fluorescent glasses prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1 were tested using a fluorescence spectrometer. The performance test results are shown in Table 2. Among them, the emission spectrum of Example 1 is shown in Table 2. Figure 2 , excitation spectrum see Figure 3 Under the excitation of blue light with a wavelength of 465nm, there is fluorescence emission at 570nm-710nm, and the emission peak is at 613nm.

[0100] The visible light transmittance was tested by a spectrophotometer, and the results are shown in Table 2. Among them, the visible light transmittance test curve of Example 1 is shown in Figure 4 .

[0101] Table 1

[0102] serial number Red fluorescent glass material composition Example 1 <![CDATA[0.7CaO·0.15Y 2 THE 3 ·0.8SiO 2 ·0.2GeO 2 ·0.035Eu 2 THE 3 ]]> Example 2 <![CDATA[0.7CaO·0.15Y 2 THE 3 ·0.9SiO 2 ·0.1GeO 2 ·0.035Eu 2 THE 3 ]]> Example 3 <![CDATA[0.7CaO·0.15Y 2 O 3 ·0.7SiO 2 ·0.3GeO 2 ·0.035Eu 2 O 3 ]]> Example 4 <![CDATA[0.7CaO·0.15Y 2 O 3 ·0.6SiO 2 ·0.4GeO 2 ·0.035Eu 2 O 3 ]]> Example 5 <![CDATA[0.7CaO·0.15Y 2 ZERO 3 ·0.5SiO 2 ·0.5GeO 2 ·0.035Eu 2 ZERO 3 ]]> Comparative Example 1 <![CDATA[0.7CaO·0.15Y 2 THE 3 SiO 2 ·0.035Eu 2 THE 3 ]]>

[0103] Table 2

[0104]

[0105] Note: In Table 2, the relative luminous intensity is based on the luminous intensity of Example 1, which is set as 100%. The luminous intensity of other examples and comparative examples is compared with that of Example 1.

[0106] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A red fluorescent glass material, characterized in that: It has a chemical composition as shown in formula (1): aMO·bY2O3·cSiO2·dRO2·xEu2O3(1), wherein, M is selected from one or more of Ca, Sr, and Ba, and R is selected from one or more of Zr, Ti, and Ge; a represents the molar coefficient of MO, 0 < a < 1; b represents the molar coefficient of Y2O3, 0 < b < 1; c represents the molar coefficient of SiO2, 0 < c < 1; d represents the molar coefficient of RO2, 0 < d < 1; x represents the molar coefficient of Eu2O3, 0 < x < 0.

1.

2. The red fluorescent glass material according to claim 1, characterized in that: M is selected from one of Ca, Sr, and Ba.

3. The red fluorescent glass material according to claim 1, characterized in that: R is selected from one of Zr, Ti, and Ge.

4. The red fluorescent glass material according to claim 1, characterized in that: 0.1 < a < 0.9, 0.05 < b < 0.

5.

5. The red fluorescent glass material according to claim 1, characterized in that: 0.05 < c < 1, 0.01 < d < 0.

9.

6. The red fluorescent glass material according to claim 1, characterized in that: 0.005<x<0.1。 7. The red fluorescent glass material according to claim 1, characterized in that: It has a chemical composition as shown in any of the following: 0.7CaO·0.15Y2O3·0.8SiO2·0.2GeO2·0.035Eu2O3; 0.7CaO·0.15Y2O3·0.9SiO2·0.1GeO2·0.035Eu2O3; 0.7CaO·0.15Y2O3·0.7SiO2·0.3GeO2·0.035Eu2O3; 0.7CaO·0.15Y2O3·0.6SiO2·0.4GeO2·0.035Eu2O3; 0.7CaO·0.15Y2O3·0.5SiO2·0.5GeO2·0.035Eu2O3.

8. A method for preparing the red fluorescent glass material according to any one of claims 1 to 7, characterized in that: It includes the following steps: 1) Mix each raw material according to the chemical composition to obtain a mixture; calcine the mixture at 1200 - 1800 °C for 1 - 10 h to obtain a calcined product; 2) Cast the calcined product to obtain a glass product; 3) Further heat-treat the glass product at 300 - 800 °C to obtain a red fluorescent glass material.

9. The method according to claim 8, characterized in that The calcination temperature is 1300 - 1700 °C, and the calcination time is 1 - 8 h.

10. Use of a red fluorescent glass material as described in any one of claims 1 - 7 in the packaging of light-emitting diodes.

Citation Information

Patent Citations

  • Red silicon-aluminum oxynitride fluorescent material and preparation method thereof

    CN103484110A

  • Red luminescent glass material and preparation method thereof

    CN104150763A

  • Europium ion doped red light fluorescent powder for white light LED and preparation method thereof

    CN109628092A

  • Fluorescent glass, and preparation method and application thereof

    CN113387565A

  • Red fluorescent material, and preparation method and application thereof

    CN113388395A